2015
DOI: 10.1002/jor.22874
|View full text |Cite
|
Sign up to set email alerts
|

T2* relaxometry and volume predict semi‐quantitative histological scoring of an ACL bridge‐enhanced primary repair in a porcine model

Abstract: Magnetic resonance imaging (MRI) variables, such as T2* and volume, can predict the healing ligament structural properties. How these MR variables relate to semi-quantitative histology of the healing ACL is yet unknown. We hypothesized that T2* and volume would predict the histological scoring of a healing ACL. Yucatan minipigs underwent ACL transection and received: bridge-enhanced ACL repair or no treatment. The surgical legs were harvested after 52 weeks and imaged using a high resolution 2-echo sequence. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 16 publications
(40 reference statements)
2
60
0
Order By: Relevance
“…that the median T 2 * relaxation of healing ACL after surgery falls within the range of 7-16 ms, 14 which can be nearly twice as long as the median T 2 * of intact ligament at 8.5 ± 0.6 ms. 13 Furthermore, we have shown that these relaxation times correlate with semi-quantitative histology measures. 49 The increase in median ACL T 2 * relaxation times in Figure 1B corroborates the findings of these earlier studies. We therefore believe that the gradient echo sequence described here is well-suited for capturing relevant changes in MR T 2 * relaxation times that are characteristic of healing ligament within 6 months after ACL repair.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…that the median T 2 * relaxation of healing ACL after surgery falls within the range of 7-16 ms, 14 which can be nearly twice as long as the median T 2 * of intact ligament at 8.5 ± 0.6 ms. 13 Furthermore, we have shown that these relaxation times correlate with semi-quantitative histology measures. 49 The increase in median ACL T 2 * relaxation times in Figure 1B corroborates the findings of these earlier studies. We therefore believe that the gradient echo sequence described here is well-suited for capturing relevant changes in MR T 2 * relaxation times that are characteristic of healing ligament within 6 months after ACL repair.…”
supporting
confidence: 89%
“…While UTE sequences have demonstrated sensitivity to changes in intact tendon and ligament ultrastructure with measured T 2 * relaxation times on the order of 3–14.8 ms, we have previously shown that the median T 2 * relaxation of healing ACL after surgery falls within the range of 7–16 ms, which can be nearly twice as long as the median T 2 * of intact ligament at 8.5 ± 0.6 ms . Furthermore, we have shown that these relaxation times correlate with semi‐quantitative histology measures . The increase in median ACL T 2 * relaxation times in Figure B corroborates the findings of these earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the extent that T 2 * relaxation times were sensitive to the more clinically applicable scan conditions versus the conditions that we have used previously in our research (Biercevicz, et al, 2015; Biercevicz, et al, 2014), T 2 * relaxation times derived from in vivo 384×384 matrix resolution were compared to those derived from in situ 512×512 matrix resolution scan conditions. Scanning ACLs at high resolution in situ within 60 minutes of euthanasia led to decreased and more variable T 2 * relaxation times compared to in vivo moderate resolution scans.…”
Section: Discussionmentioning
confidence: 99%
“…T 2 * is a measure of MR signal relaxation that is related to the degree of free water bound by collagen (Helms, et al, 2008), with highly organized collagen structures yielding shorter T 2 * relaxation times (Williams, et al, 2012). T 2 * is particularly well suited for imaging ligament and tendon healing in vivo because collagen re-organization is of interest (Biercevicz, et al, 2015; Weiler, et al, 2001). We have previously demonstrated that a larger volume of the anterior cruciate ligament (ACL) containing short MR T 2 * relaxation times predicts the ligament structural properties in a minipig model of bridge-enhanced ACL repair (Biercevicz, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation